Estudio de prefactibilidad para la instalación de una planta productora de infusión filtrante de jengibre (Zingiber officinale) deshidratado en polvo con stevia rebaudiana - Córdova Córdova, Carlos Andrés (2020)
The purpose of this research is to determine the commercial, technical, economic, financial and social viability for the installation of a processing plant of infusion filters of dehydrated ginger and stevia. The problem detected is that the Peruvian exports of ginger is made as raw material (whole ginger or pieces) and no value is added. On the other hand, there is currently a worldwide trend towards the consumption of healthy and natural products, low in calories and rich in antioxidants, of which Peru is no stranger, and the drinking infusions of natural species and herbs comply with what the consumers demand, for which the present project has been developed. At present, there is no Peruvian company that produces ginger filters, but there are imports of the product, so there is a market that will accept the product, which is introduced as a beverage with healing properties by its ingredients composition, which help mainly to treat digestive and respiratory diseases. Filters of dehydrated ginger with Stevia will be sold in filter bags of 1g of content and presented in boxes of 25 units. The target market will be people over 26 years of B and C SES of Lima Metropolitana. The demand for the project was determined at 14,045 kg for the first year and 20,885 kg for the last year. After conducting the location study, it was determined that the industrial plant will be located in the city of Lima, specifically in the Lurin district. The plant size was determined by the size - market relationship and was 20,885 kg/year. The capacity of the productive plant will be 27,720 kg/year. The total investment required will be 594,982 PEN, with 60% contributed by the shareholders and 40% financed by the Corporación Financiera de Desarrollo. Finally, after the corresponding analysis, it was determined that the project generates positive economic and financial results, presenting a financial NPV of 591,455 PEN, a financial IRR of 60%, a benefit/cost ratio of 2.82, and a recovery period of 2 years and 4 months. Likewise, the project is socially profitable, generating 8.03 PEN of added value for each 1 PEN invested.